Communication Problems When Participants Disagree (or Avoid Disagreeing) in Dialogues in Swedish Natural Resource Management—Challenges to Agonism in Practice - Hallgren, Lars; Bergeå, Hanna; Westberg, Lotten (Frontiers in Communication, 2018)
In this article, we analyze how participants perform disagreement in meetings organized with the explicit purpose of managing through dialogue conflicts concerning natural resources in Sweden. How is a conversation initiated about something that participants disagree about? How do they clarify to each other that, about what, and why they disagree? How do they show that they understand it is like that and what do they do when this is clear to them? Answers to these questions are important because, if dialogue is to contribute to the constructive development of conflict situations, dialogue should be regarded as a forum where disagreement is expressed and developed, rather than as a forum and tool for consensus. We conducted a sequential analysis of how disagreement is performed and accomplished in normative dialogues in which participants talk about how to reduce the negative impact of wildlife populations—such as predators and grazing birds—on human activities such as domestic reindeer husbandry and crop farming. The analysis shows that disagreement is articulated in ways that do not seem to make ontological, epistemological and axiological differences among positions clear for participants. We identified six procedures through which disagreements are (not) accomplished in these conversations. This shows that routines and procedures in normative dialogue are characterized by consensus-preferences not helpful for agonistic dialogue. In order to avoid situations where dialogue leads to discursive closures, standards and procedures that facilitate articulation of disagreement need to be developed.